2021
DOI: 10.3390/app112411813
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Chloroformic Extract from Salvia connivens (Lamiales: Lamiaceae) and Its Principal Compounds against Spodoptera frugiperda (Lepidoptera: Noctuidae)

Abstract: Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) is one of the most damaging pests in maize crops. In order to manage it, synthetic insecticides such as diamides, neonicotinoids, and pyrethroids are used, but they present a risk for humans and the environment. Investigations of safer alternatives include the use of natural extracts. Thus, this research evaluated the effects of chloroform extract (CHCl3Sc) (5000, 4000, 2000, 1000, and 500 ppm) on aerial parts of Salvia connivens and of nonanal and pyrocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Walnut fruits contain high relative levels of nonanal and methyl salicylate, which have been shown to elicit the EAG response in codling moths in previous studies [ 25 ] and also showed strong attraction to females according to the olfactory behavior bioassay in this study. Nonanal is attractive to many Lepidoptera [ 39 , 40 ], which also specifically attracts females of Helicoverpa assulta (Lepidoptera: Noctuidae) and Grapholita molesta (Lepidoptera: Tortricidae) [ 41 , 42 ] and enables codling moth larvae to aggregate [ 43 ]. Methyl salicylate is widespread in many plants and is a metabolite associated with the salicylic acid pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Walnut fruits contain high relative levels of nonanal and methyl salicylate, which have been shown to elicit the EAG response in codling moths in previous studies [ 25 ] and also showed strong attraction to females according to the olfactory behavior bioassay in this study. Nonanal is attractive to many Lepidoptera [ 39 , 40 ], which also specifically attracts females of Helicoverpa assulta (Lepidoptera: Noctuidae) and Grapholita molesta (Lepidoptera: Tortricidae) [ 41 , 42 ] and enables codling moth larvae to aggregate [ 43 ]. Methyl salicylate is widespread in many plants and is a metabolite associated with the salicylic acid pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These were chosen after completing the logarithmic bioassay. The selection criteria were the minimum and maximum biological response and then three concentrations were selected between them, and they were: 5000, 4000, 2000, 1000, 500, and 0 ppm, according to our previous studies [35,36], adding each concentration during the preparation of the artificial diet for S. frugiperda. To carry out the test, 20 #0 polyethylene PRIMO brand cups (Ecatepec, Mexico) were used, in which a piece of the food with an approximate volume of 1 cm 3 containing the corresponding concentration of each extract of R. communis was placed.…”
Section: Evaluation Of the Biological Activity Of The Methanolic And ...mentioning
confidence: 99%